The mediating role of safety behavior in the relationship between safety climate and safety outcomes among sanitary workers in Pakistan - Nisar, Nadia; Saat, Nur Zakiah Mohd; Nata, Dayana Hazwani Mohd Suadi; Kamaludin, Nurul Farahana; Ishak, Ismarulyusda; Ahmad, Abdul Momin Rizwan (Frontiers in Public Health, 2025)
IntroductionSanitary workers are regarded as the foundation of society due to their essential role in maintaining cleanliness and hygiene. In Pakistan, sanitation tasks are conducted manually, resulting in adverse health consequences for workers.ObjectiveThis research intends to investigate the relationship between safety climate and safety outcomes among sanitary workers along with the mediating influence of safety behavior.MethodsThe data was collected from two sanitation organizations in Punjab, Pakistan. The data was subsequently analyzed using SPSS version 27.0 and SmartPLS version 4. The participants were chosen from the cantonment board Attock and Lahore management company using a simple random sampling technique.Results/conclusionThe findings revealed that safety climate and its dimensions such as management commitment, safety communication learning trust, and work environment have a significant positive relationship with safety outcomes. Similarly, safety behavior significantly mediates the relationship between safety climate, dimensions and safety outcomes.